Permeation Peptide Conjugates for In Vivo Molecular Imaging Applications - Kristin E. Bullok; Seth T. Gammon; Stefania Violini; Andrew M. Prantner; Victor M. Villalobos; Vijay Sharma; David Piwnica-Worms (Molecular Imaging)
Rapid and efficient delivery of imaging probes to the cell interior using permeation peptides has enabled novel applications in molecular imaging. Membrane permeant peptides based on the HIV-1 Tat basic domain sequence, GRKKRRQRRR, labeled with fluorophores and fluorescent proteins for optical imaging or with appropriate peptide-based motifs or macrocycles to chelate metals, such as technetium for nuclear scintigraphy and gadolinium for magnetic resonance imaging, have been synthesized. In addition, iron oxide complexes have been functionalized with the Tat basic domain peptides for magnetic resonance imaging applications. Herein we review current applications of permeation peptides in molecular imaging and factors influencing permeation peptide internalization. These diagnostic agents show concentrative cell accumulation and rapid kinetics and display cytosolic and focal nuclear accumulation in human cells. Combining methods, dual-labeled permeation peptides incorporating fluorescein maleimide and chelated technetium have allowed for both qualitative and quantitative analysis of cellular uptake. Imaging studies in mice following intravenous administration of prototypic diagnostic permeation peptides show rapid whole-body distribution allowing for various molecular imaging applications. Strategies to develop permeation peptides into molecular imaging probes have included incorporation of targeting motifs such as molecular beacons or protease cleavable domains that enable selective retention, activatable fluorescence, or targeted transduction. These novel permeation peptide conjugates maintain rapid translocation across cell membranes into intracellular compartments and have the potential for targeted in vivo applications in molecular imaging and combination therapy.